Assessment of new solar radiation nowcasting methods based on sky-camera and satellite imagery. (15th June 2021) - Rodríguez-Benítez, Francisco J.; López-Cuesta, Miguel; Arbizu-Barrena, Clara; Fernández-León, María M.; Pamos-Ureña, Miguel Á.; Tovar-Pescador, Joaquín; Santos-Alamillos, Francisco J.; Pozo-Vázquez, David
Abstract: This work proposes and evaluates methods for extending the forecasting horizon of all-sky imager (ASI)-based solar radiation nowcasts and estimating the uncertainty of these predictions. In addition, we evaluated procedures for improving the temporal resolution and latency of satellite-imagery-derived solar nowcasts. Based on these contributions, we assessed the reliability of ASIs and satellite-derived solar radiation nowcasts, with 1-min time-resolution and up-to-90-min ahead. The study was conducted in a location in Southern Spain using a set of cloudy days, specifically selected as representative of the most challenging conditions regarding solar radiation nowcasting. The results reveal that the use of ASI-based models provide low benefits compared to the use of satellite-based models for point solar radiation nowcasting. Given the frequency of occurrence of the different sky types in the study area, the results suggest that the use of a simple smart persistence algorithm, in combination with a low-resolution satellite nowcasting model could be an adequate choice, avoiding the challenges associated with the use of ASIs. Highlights: New methods for extending forecasting horizon of sky camera based solar nowcasting. Sky camera solar nowcasting uncertainty assessed. One minute time resolution satellite-imagery model solar nowcasting. Sky camera provides low added value compared to the use of satellite imagery. Smart-Persistence plus satellite-imagery models as the best option for solar nowcasting.